Production, properties and trends in development of biodegradable polyesters with particular respect to aliphatic-aromatic copolymers - Ukielski, R.; Kondratowicz, F.; Kotowski, D. (Polimery, 2013)
The paper is a literature review concerning the industrially produced aliphatic-aromatic copolyesters (AAC) and aliphatic polyesters capable of degradation. Particular attention was given to worldwide studies on new types of aliphatic-aromatic copolymers.